Literasi AI dan Keterbukaan Diri Digital Siswa SMP di Era Kecerdasan Buatan: Analisis Model PLS-SEM - Atika Juniwati; Erisa Kurniati; Indryani Indryani (Scidacplus, 2026)
This study aims to analyze the relationship between artificial intelligence literacy (AI literacy) and junior high school students’ digital self-disclosure in the era of artificial intelligence. The increasing phenomenon of students’ emotional interactions with AI-based systems such as ChatGPT indicates that technology is no longer merely a learning tool, but also a space for self-expression. Employing an explanatory quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, this study involved 243 students who are accustomed to interacting with AI applications in both academic and personal contexts. The conceptual model was developed through the integration of the AI literacy framework proposed by Wang, Rau, and Yuan (2022), comprising awareness, usage, evaluation, and ethics, and the digital self-disclosure framework by Merwin et al. (2025), which includes personal sharing, comfort, trust, and preference for AI. The findings reveal that eight out of fourteen hypothesized relationships are statistically significant. The dimensions of AI awareness and usage positively influence students’ comfort and trust in AI, while the ethical dimension functions as a regulatory factor that restrains excessive self-disclosure. Emotional factors, particularly feelings of comfort and trust, are found to serve as the primary bridge between students’ cognitive abilities and their digital behavior. These findings highlight that AI literacy not only reflects technological competence but also encompasses ethical and emotional awareness in human–AI interactions. This study recommends that AI literacy education in secondary schools should not be limited to technical proficiency, but should also emphasize the development of empathetic, reflective, and responsible digital character in an increasingly digitalized world.